Collaborative challenges during transition of patients with severe depression from secondary mental health services to primary care and opportunities for improvement - a qualitative study - Aggestrup, Anne Sofie; Kousgaard, Marius Brostrøm; Martiny, Klaus; Davidsen, Annette Sofie (Frontiers in Psychiatry, 2025)
IntroductionPatients with severe depression are treated across primary and secondary healthcare and receive employment support from municipal caseworkers (CWs). However, collaboration during the transition from outpatient secondary mental health services to primary care is often insufficient, increasing the risk of relapse. Limited knowledge exists on how health professionals (general practitioners (GPs), mental health professionals (MHPs) and social medicine physicians), CWs, and patients perceive barriers – and, in particular, how collaboration could be improved and relapse prevented. We aimed to explore barriers to cross-sectoral collaboration during the transition of patients with severe depression from outpatient secondary mental health services to primary care, and to generate ideas from health professionals, CWs, and patients to enhance this collaboration and contribute to preventing relapse.Materials and methodsThis qualitative study included fieldwork observations, interviews, focus groups, and workshops with 25 health professionals, seven CWs, and four recently discharged patients. Data was analysed using Interpretative Phenomenological Analysis and descriptive methods.ResultsFour themes were found: Insufficient communication from mental health services caused challenges for GPs in the handover phase; Different goals between professionals resulted in mutual mistrust and blame; Patients felt left on their own after discharge due to a lack of coordination and support services and; Ideas for improving cross-sectoral collaboration. Collaboration across sectors was impeded by low relational coordination, including divergent goals, unclear roles, mutual mistrust and limited communication. An asymmetry in dependence between sectors was evident: GPs and CWs were dependent on information from MHPs during and after outpatient treatment, whereas MHPs were neither aware of this need nor expected ongoing updates. Patients felt vulnerable post-discharge, with little support, and the burden of navigating a complex healthcare system on their own. To improve collaboration, participants suggested online planning meetings, a coordinating liaison or care manager, and a smartphone application for patients to monitor their mental health and signs of relapse. Flexible return to work solutions were also emphasised.DiscussionCross-sectoral collaboration in the care of severe depression is challenged by structural and relational barriers, leaving patients vulnerable and at increased risk of relapse during transitions between sectors. Strengthening coordination through shared planning, clearer roles, a coordinating liaison or care manager, digital tools, and flexible return-to-work solutions may ensure continuity and prevent relapse of depression.